Gendered and Racialized Perceptions of Faculty Workloads. Issue 3 (June 2021) - Misra, Joya; Kuvaeva, Alexandra; O'meara, Kerryann; Culpepper, Dawn Kiyoe; Jaeger, Audrey
Faculty workload inequities have important consequences for faculty diversity and inclusion. On average, women faculty spend more time engaging in service, teaching, and mentoring, while men, on average, spend more time on research, with women of color facing particularly high workload burdens. We explore how faculty members perceive workload in their departments, identifying mechanisms that can help shape their perceptions of greater equity and fairness. White women perceive that their departments have less equitable workloads and are less committed to workload equity than white men. Women of color perceive that their departments are less likely to credit their important work through departmental rewards systems than white men. Workload transparency and clarity, and consistent approaches to assigning classes, advising, and service, can reduce women's perceptions of inequitable and unfair workloads. Our research suggests that departments can identify and put in place a number of key practices around workload that will improve gendered and racialized perceptions of workload.